Agromorphological Evaluation of 44 lines of Mung Bean (Vigna radiata (L.) Wilczek) Introduced in Burkina Faso - Wend-Pagnagde Félicien Marie Serge Zida; Teyoure Benoit Joseph Batieno; Tinga Jeremy Ouedraogo; Mahamadou Sawadogo (European Scientific Journal, ESJ, 2021)
Mung bean (Vigna radiata L. Wilczek) is an important annual legume which is well suited to dry areas, like Burkina Faso where it is still an orphan legume. The present study was conducted to evaluate 44 mung bean genotypes introduced in Burkina Faso and to determine genetic diversity in this collection using both quantitative and qualitative traits. A field experiment was conducted in an augmented bloc design with three blocks and an extraearly maturing cowpea variety as check. Data were recorded on six (06) quantitative traits and seven (07) qualitative traits. For qualitative traits, diversity was revealed in four parameters including hypocotyl’s color, seed coat color, pods and stem pubescence. Significant genetic variability was revealed among genotypes for all the quantitative characters. Phenotypic coefficient of variation (PCV) was higher than Genotypic coefficient of variation (GCV) for all characters studied indicating the influence of environmental effect on the characters. The GCV and PCV estimates were high for number of pods per plant followed by plant height and hundred seeds weigh. The high heritability coupled with high genetic advanced as percent of mean observed for these traits suggest an important genetic gain in genetic improvement for these characters. The genetic diversity observed was grouped into five clusters. Mungbean lines were grouped into four clusters and the cowpea variety used as check crop in this trial was clustered apart. This genetic diversity, both qualitatively and quantitatively, will help enrich local biodiversity in terms of legumes in general and mung bean in particular and constitutes an important basis for a future mungbean breeding program.